2003
DOI: 10.1021/bi034446e
|View full text |Cite
|
Sign up to set email alerts
|

Effects of DNA Adduct Structure and Sequence Context on Strand Opening of Repair Intermediates and Incision by UvrABC Nuclease

Abstract: DNA damage recognition of nucleotide excision repair (NER) in Escherichia coli is achieved by at least two steps. In the first step, a helical distortion is recognized, which leads to a strand opening at the lesion site. The second step involves the recognition of the type of chemical modification in the single-stranded region of DNA during the processing of the lesions by UvrABC. In the current work, by comparing the efficiencies of UvrABC incision of several types of different DNA adducts, we show that the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
43
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 36 publications
9
43
0
Order By: Relevance
“…The 0-C stands for unmodified DNA with no bending (no carbon tether). Pane B: XPC-HR23B complex (labeled as XPC) had high affinities to DNA bending with the following order: 2-C > 3-C > 4-C > 0-C, which is consistent with the order of their bending-angles: 2-C > 3-C > 4-C > 0-C. Panel C: Binding of E. coli UvrA to the same DNA bending substrates (27)(28)(29).…”
Section: Discussionsupporting
confidence: 57%
“…The 0-C stands for unmodified DNA with no bending (no carbon tether). Pane B: XPC-HR23B complex (labeled as XPC) had high affinities to DNA bending with the following order: 2-C > 3-C > 4-C > 0-C, which is consistent with the order of their bending-angles: 2-C > 3-C > 4-C > 0-C. Panel C: Binding of E. coli UvrA to the same DNA bending substrates (27)(28)(29).…”
Section: Discussionsupporting
confidence: 57%
“…25 This finding represents a case where the same lesion is excised with different efficiencies in two different, natural DNA sequence contexts. A similar sequence context dependence was observed in the excision of C8-guanine adducts of 2-aminofluorene and N-acetyl-2-aminofluorene catalyzed by UvrABC from Escherichia coli, 22 and other base sequence effects on the excision of these lesions have also been reported. 23 Ruan et al attributed their observed sequence effects to the overall weaker base stacking and weaker hydrogen bonding interactions associated with A:T rather than G:C base pairs flanking the lesion.…”
Section: Introductionsupporting
confidence: 64%
“…17,[19][20][21] Thus, the biological processing of such lesions by DNA polymerases and the cellular DNA repair machinery may be determined by the sequence-dependent conformational state of the DNA lesion. 20,[22][23][24] The relative rate of NER of a DNA adduct and therefore its mutagenic potential can depend on the nature of the neighboring bases, producing mutational hotspots and coldspots. 17,19,20,[22][23][24][25] Remarkable sequence-dependent conformational equilibria have been noted in solution NMR studies 17 of mutagenic DNA adducts derived from the polycyclic aromatic hydrocarbon benzo[a]pyrene (BP), an environmental precarcinogen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3, several minor incisions were also observed on the 5' side of the major incision, which are further away from the adduct. Similar 5' extra cuts by UvrABC have also been described previously for other DNA adducts (Moolenaar et al, 1998;Zou et al, 2003). No specific incision(s) was detected for the unmodified 40-mer under the same UvrABC concentration used (Fig.…”
Section: Uvrabc Incision Of the Oligonucleotide Containing N 2 -4-hopsupporting
confidence: 84%